Upper Mantle Structure beneath the Mid-Ocean Ridges in Indian Ocean: Insights from the Seismic Tomography Models - Yana Yu; Xing Yu; Hu He; Zhaocai Wu; Zakaria A. Khamis; El-Gharabawy Suzan; Hang Hu; Huichen Li (Journal of Earth Science, 2026)

Mantle End-Member Distribution Characteristics of Hotspots in the South Atlantic Based on Dimensionality Reduction and Clustering - Huichen Li; Xing Yu; Hu He; Yana Yu; Hang Hu; Xucheng Xu (Journal of Marine Science and Engineering, 2026)
The South Atlantic is a classic region of hotspot volcanism, with numerous intraplate magmatic structures, such as the Walvis Ridge, Rio Grande Rise, Fernando de Noronha Ridge, and Victoria-Trinda Ridge. These structures record mantle plume activity and plate tectonics since the breakup of the South America–Africa continent, but the spatiotemporal correlations of mantle end-members among different hotspot systems remain unclear. This paper uses the Unified Manifold Approximation and Projection Algorithm (UMAP) and Hierarchical Agglomeration Clustering Algorithm (HAC) to perform dimensionality reduction and cluster analysis on 288 basalt Sr-Nd-Pb isotope data from 12 major hotspot-derived seamount chains/rises in the South Atlantic, identifying three types of mantle end-members: EM-type, HIMU-type, and PREMA/FOZO-type. The results show that HIMU-type end-members are mainly distributed in St. Helena Island and its associated Guinea seamount chain; EMI-type end-members dominate the Walvis Ridge basement, Rio Grande Rise, and discovered seamount chain; and PREMA/FOZO-type end-members are mainly distributed in the Brazilian continental margin seamount chain. In terms of time series, EM-type magmatic activity began in the Early Cretaceous (~132 Ma), while HIMU-type hotspot activity appeared later (~82 Ma), and both were vertically superimposed on the Walvis Ridge basement. Based on the spatiotemporal distribution characteristics of mantle end-members in hotspots in the South Atlantic and Indian Oceans, this paper proposes a two-stage magmatism model for hotspots at the African margin: in the early stage, EM-type material, associated with continental delamination and ancient lithosphere recycling, preferentially melted, forming large-scale submarine plateaus or seamount chains; in the later stage, HIMU-type material, associated with the reactivation of subducted oceanic crust or Archean carbonated subcontinental lithospheric mantle (SCLM), melted and rose in weak areas of mature oceanic crust, forming smaller seamounts. This study provides a new perspective on the unified genetic mechanism of multiple hotspots in the South Atlantic and offers a reference for understanding the generation, evolution, and magmatic activity of hotspots during the breakup of Gondwana.

GRP78 interacts with the Nsp3 of porcine deltacoronavirus and inhibits viral replication - Zhengxin Liu; Ruiming Yu; Liping Zhang; Yuhan Wen; Dongsheng Wang; Xinru Wang; Zhongwang Zhang; Peng Zhou; Xiaohua Du; Huichen Guo; Li Pan; Xia Liu; et al. (Veterinary Microbiology, 2026)

Adaptation Mechanisms of Aquatic Animals to Saline–Alkaline Water Aquaculture: Physiological, Energetic and Molecular Perspectives - Yingsha Qu; Huichen Li; Bo Zhang; Hongwu Cui; Jianlei Chen; Yong Xu; Zhengguo Cui; Keming Qu; Hao Li (Fishes, 2026)
Saline–alkaline water constitutes a vital strategic non-traditional fishery resource in China, characterized by high pH values, elevated carbonate alkalinity, and complex ionic compositions. These extreme environmental conditions impose significant stress on aquatic animals, mainly by inducing ionic toxicity and disrupting acid–base regulatory mechanisms. Such disruptions subsequently lead to osmotic imbalance, metabolic dysregulation, and immunosuppression, thus restricting the survival and growth of aquatic species in aquaculture systems. Consequently, the sustainable development of the saline–alkaline aquaculture is imperative for enhancing production efficiency and promoting the utilization of marginal land and water resources. This review comprehensively summarizes the current status of saline–alkaline aquaculture and highlights the stress-inducing impacts of salinity, alkalinity, and specific ionic ratios on teleost fishes and crustaceans. It further explores key adaptive mechanisms, including osmoregulatory and ionoregulatory strategies, bioenergetic trade-offs related to oxygen consumption and ammonia excretion, coordinated antioxidant and innate immune responses, as well as recent findings from multi-omics research. This review aims to offer a scientific foundation for the selection and breeding of saline–alkaline-tolerant strains, the precise regulation of aquaculture water environments, and the development of ecological aquaculture models in saline–alkaline regions, thereby facilitating the sustainable utilization of saline–alkaline land and water resources.

Molecular characterization of Spodoptera frugiperda nose resistant to fluoxetine protein 6 and its putative involvement in tolerance to cyantraniliprole - Jiaping Wei; Changpeng Liu; Daojie Guan; Zhichao Wang; Huichen Ge; Hai Li; Hainan Zhang; Kun Qian; Jianjun Wang (Pesticide Biochemistry and Physiology, 2025)

Cyclophilin A promotes porcine deltacoronavirus replication by regulating autophagy via the Ras/AKT/NF-κB pathway - Yousheng Peng; Chenchen Li; Liping Zhang; Ruiming Yu; Yonglu Wang; Li Pan; Huichen Guo; Yanming Wei; Xinsheng Liu (Veterinary Microbiology, 2024)

Multi-metal Exposure and Liver Function in Elderly with Diabetes Mellitus: A Cross-Sectional Study in Eastern China - Jiujing Lin; Jia Li; Huichen Yao; Jinjie He; Xiangsheng Xue; Hengxia Zhao; Chenyang Hou; Xiaomei Li; Qingzhi Hou (Exposure and Health, 2024)

A novel recombination porcine epidemic diarrhea virus isolated from Gansu, China: Genetic characterization and pathogenicity - Linjie Li; Bingqing Li; Jin Wang; Lei Liu; Yi Li; Shiqi Sun; Shuanghui Yin; Liping Zhang; Xinsheng Liu; Xingang Xu; Huichen Guo (Veterinary Microbiology, 2024)

Autophagy inhibition mediated by trillin promotes apoptosis in hepatocellular carcinoma cells via activation of mTOR/STAT3 signaling - Guangjie Zhan; Tiantian Wei; Huichen Xie; Xiaoming Xie; Jun Hu; Hao Tang; Yating Cheng; Huaifeng Liu; Shujing Li; Guohua Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

3D-exosomes laden multifunctional hydrogel enhances diabetic wound healing via accelerated angiogenesis - Han Peng; Huichen Li; Xi Zhang; Jiezhang Tang; Yongping Liang; Lipeng Qiao; Yun Zhu; Mengmeng Hou; Siming Wei; Zhaoxiang Zhang; Chaohua Liu; Xinmao Li; et al. (Chemical Engineering Journal, 2023)

Determination of Alkylphenols in Atmospheric Fine Particulates in Taiyuan and Guangzhou based on atmospheric pressure gas chromatography-tandem mass spectrometry - Fangjie Wang; Xiaoning Chen; Huichen Li; Bowen Huang; Yu He; Zongwei Cai (Atmospheric Environment, 2023)

Effect of paste processing on residue levels of imidacloprid, pyraclostrobin, azoxystrobin and fipronil in winter jujube - Wei Peng; Liuwei Zhao; Fengmao Liu; Jiaying Xue; Huichen Li; Kaiwei Shi (Food Additives & Contaminants: Part A, 2014)

Transfer of difenoconazole and azoxystrobin residues from chrysanthemum flower tea to its infusion - Jiaying Xue; Huichen Li; Fengmao Liu; Jian Xue; Xiaochu Chen; Jing Zhan (Food Additives & Contaminants: Part A, 2014)